15th International Podocyte Conference, Hamburg, Germany, June 11-13, 2025. Abstracts: From Glomerular Biology to Glomerular Medicine - Laurel Damashek (Glomerular Diseases)

(untitled)
Over the past decades, the trajectory of podocyte biology and glomerular medicine has evolved into a globally connected, interdisciplinary field at the interface of cell biology, systems medicine, and clinical nephrology. The insight that the podocyte is not merely a structural component, but a key orchestrator of glomerular integrity and function, has fundamentally transformed our understanding of glomerular health and disease. From early discoveries in cell architecture and signaling to the identification of podocyte-specific genes and the application of high-resolution imaging and omics technologies, each milestone has opened new avenues of investigation. Today, podocyte biology informs diagnostic frameworks, contributes to biomarker development, guides clinical trial design, and supports current and future targeted therapies. Building on the community’s combined achievements, the International Podocyte Meeting has evolved into the main meeting of the International Society of Glomerular Disease (ISGD)—bringing together podocyte biology, glomerular biology, glomerular diseases, and glomerular medicine. This progression—spanning fundamental research, translational approaches, and patient-centered therapy—is also reflected in this abstract compilation. Advancing research relies on global exchange between experts from diverse disciplines, which the International Podocyte Conference has enabled since its 1999 inauguration. We are particularly grateful to all participants joining us this year and acknowledge the many organizations and sponsors whose support has helped make this conference possible. We are especially thankful for the continued partnership with NephCure, which has always played a key role in aligning podocyte research with patient-centered goals. We thank ISGD for supporting this meeting and helping to establish podocyte biology within a broader institutional framework. Our appreciation also goes to our local organizing team and host institutions for their effective and collegial cooperation. With this compilation, we hope to inspire rich discussion, promote collaboration, and attract the next generation of researchers to the field of podocyte biology and glomerular medicine.